Genetic interactions between diverged alleles of Early heading date 1 (Ehd1) and Heading date 3a (Hd3a)/ RICE FLOWERING LOCUS T1 (RFT1) control differential heading and contribute to regional adaptation in rice (Oryza sativa). Issue 3 (11th June 2015) - Zhao, Jing; Chen, Hongyi; Ren, Ding; Tang, Huiwu; Qiu, Rong; Feng, Jinglei; Long, Yunming; Niu, Baixiao; Chen, Danping; Zhong, Tianyu; Liu, Yao‐Guang; Guo, Jingxin
Summary: Initiation of flowering, also called heading, in rice ( Oryza sativa ) is determined by the florigens encoded by Heading date 3a ( Hd3a ) and RICE FLOWERING LOCUS T1 ( RFT1 ). Early heading date 1 ( Ehd1 ) regulates Hd3a and RFT1 . However, different rice varieties have diverged alleles of Ehd1 and Hd3a/RFT1 and their genetic interactions remain largely unclear. Here we generated three segregating populations for different combinations of diverged Ehd1 and Hd3a/RFT1 alleles, and analyzed their genetic interactions between these alleles. We demonstrated that, in an ehd1 mutant background, Hd3a was silenced, but RFT1 was expressed (although at lower levels than in plants with a functional Ehd1 ) under short‐day (SD) and long‐day (LD) conditions. We identified a nonfunctional RFT1 allele ( rft1 ); the lines carrying homozygous ehd1 and Hd3a/rft1 failed to induce the floral transition under SD and LD conditions. Like Hd3a, RFT1 also interacted with 14‐3‐3 proteins, the florigen receptors, but a nonfunctional RFT1 with a crucial E105K mutation failed to interact with 14‐3‐3 proteins. Furthermore, analyses of sequence variation and geographic distribution suggested that functional RFT1 alleles were selected during rice adaptation to high‐latitude regions. Our results demonstrate the important roles of RFT1 in rice flowering and regional adaptation.